Simultaneous construction of axial and planar chirality by gold/TY-Phos-catalyzed asymmetric hydroarylation - Pei-Chao Zhang (Nature Portfolio, 2021)
The simultaneous construction of two different types of chiralities is challenging. Here, the authors report a cationic gold-catalyzed asymmetric hydroarylation of ortho-alkynylaryl ferrocene derivatives, which enabled the simultaneous construction of axial and planar chirality.